2018
DOI: 10.1016/j.envexpbot.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and future research directions linking tree diversity to growth, survival, and damage in a global network of tree diversity experiments

Abstract: Despite considerable research demonstrating that biodiversity increases productivity in forests and regulates herbivory and pathogen damage, there remain gaps in our understanding of the shape, magnitude, and generality of these biodiversity-ecosystem functioning (BEF) relationships. Here, we review findings from TreeDivNet, a global network of 25 tree diversity experiments, on relationships between levels of biodiversity and (a) tree growth and survival and (b) damage to trees from pests and pathogens. Tree d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 323 publications
5
111
0
Order By: Relevance
“…Cross experiment comparisons will provide tests of tree diversity effects on ecosystem functioning in different environmental contexts and will enable local truths to be separated from general patterns in BEF relationships (Grossman et al. ). The network currently consists of 25 experiments comprised of >1,100,000 trees across four biomes (Paquette et al.…”
Section: Investigating Links Between Biodiversity and Ecosystem Functmentioning
confidence: 99%
“…Cross experiment comparisons will provide tests of tree diversity effects on ecosystem functioning in different environmental contexts and will enable local truths to be separated from general patterns in BEF relationships (Grossman et al. ). The network currently consists of 25 experiments comprised of >1,100,000 trees across four biomes (Paquette et al.…”
Section: Investigating Links Between Biodiversity and Ecosystem Functmentioning
confidence: 99%
“…Distance between plots is 6 m and distance between plants within plots is 3 m. Plot size, planting density, and the separation between plots fall within the range of design features of other tree diversity experiments that have measured effects on productivity and plant-insect interactions (Scherer-Lorenzen et al, 2005;Grossman et al, 2018), and significant effects of diversity have been found previously for insect communities associated with this system (e.g. Distance between plots is 6 m and distance between plants within plots is 3 m. Plot size, planting density, and the separation between plots fall within the range of design features of other tree diversity experiments that have measured effects on productivity and plant-insect interactions (Scherer-Lorenzen et al, 2005;Grossman et al, 2018), and significant effects of diversity have been found previously for insect communities associated with this system (e.g.…”
Section: Experimental Design and Plot Selectionmentioning
confidence: 99%
“…Diversity at one trophic level affects the diversity in other trophic levels (Scherber et al, ) and can have wide‐ranging implications for ecosystem functioning (Schuldt et al, ; Tilman, Isbell, & Cowles, ). While a general positive cross‐taxon relationship between plant diversity and the diversity of other taxa is firmly established through biodiversity–ecosystem functioning (BEF) experiments for both grassland (Scherber et al, ) and forest ecosystems (Grossman et al, ), the scale (Wiens, ) at which plant diversity effects operate remains unclear (Bruelheide et al, ). While BEF experiments usually manipulate plot (i.e.…”
Section: Introductionmentioning
confidence: 99%